Firm Value Factors: The Effect Of Intellectual Capital, Managerial Ownership, And Profitability - Leny Suzan; Nurul Izza Ramadhani (Jurnal Akuntansi, 2023)
Firm value is the main component of the company in making decisions related to its financial performance. This study examines the simultaneous and partial effects of intellectual capital, managerial ownership, and profitability on firm value. The sample of this investigation is the non-cyclical consumer companies sector listed on the Indonesia Stock Exchange (IDX) in the 2018 to 2021 periods. The sampling technique used was purposive sampling, so there were 76 samples from 23 companies in the consumer non-cyclical sector. The analytical method used is panel data regression, which is analyzed using Eviews 12. The results showed that intellectual capital, managerial ownership, and profitability simultaneously and partially influence firm value. This indicates that the company needs good management guided by the factors that affect its value. Therefore, this study has implications for maximizing companies' financial performance in the consumer non-cyclical sector.